ZWALCZANIE PRZESTĘPSTWA PRANIA BRUDNYCH PIENIĘDZY - Pacian, Jolanta; Pacian, Anna (Zeszyty Prawnicze, 2016)
Fighting the Crime of Money Laundering in the Context of Legal Regulations Summary The goal of the paper is to present legal regulations preventing the crime of money laundering. Legal acts describing the crime of money laundering are the following: act of June 6, 1997 of the Criminal Code; act of November 16, 2000 on preventing the introduction into the financial turnover of property which comes from illegal or unknown sources. Appointing a special financial body called the General Inspector of Financial Information imposes new obligations on financial institutions and provides many criminal sanctions for the violation of regulations. The act concerns financial means and property coming from illegal sources, that is criminal activity, as well as from unknown sources. A systemic look at current legal regulations should make the legislator elaborate on more efficient ways of fighting the crime of money laundering.